(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the effectiveness of the ELSA Speak application, an AIpowered tool, in enhancing English-speaking skills among EFL/ESL learners. It reviews research findings and user perspectives on how ELSA supports improvements in pronunciation, fluency, and overall speaking confidence. The app’s adaptive and interactive design provides personalized learning experiences that complement traditional classroom instruction. Findings from various studies show positive learner attitudes, highlighting increased motivation, accuracy in speech production, and self-directed practice. Overall, the review emphasizes the potential of ELSA Speak as a supplementary resource for developing speaking proficiency in language education